Forecasting and Trend Analysis Bus Transportation During COVID-19 in Bali Land Using Time Series Method - Budi Mardikawati; Ida Ayu Masyumi; Asep Eka Nugraha (U Karst, 2022)
Transportation functions as a link between tourist destinations. Since the COVID-19 pandemic hit, the transportation industry has experienced direct impacts. One is a decrease in transportation users due to increased travel costs. This has a direct impact on reducing public interest in visiting. This research aims to find out changes in services for inter-provincial buses in Bali during and after the pandemic. The data used is departure data: the number of autobus suppliers; the number of departing destinations; the number of trips; and the average number of passengers from January 2018 to April 2022. From this data, time series analysis and forecasting were carried out using the Minitab software. The findings of a time series study regarding the number of trips, the number of bus suppliers, and the average number of passengers have decreased over time. Still, the number of departure destinations from the island of Bali has increased. Based on the forecasting results, it is known that the number of bus suppliers and the number of departure destinations has increased. However, it does not match the data for January 2018. This shows that the connectivity of Bali Island and the surrounding islands has increased after the COVID-19 pandemic subsided. It is hoped that it can be used as material for formulating public transportation strategies and policies, especially inter-provincial bus services.